CompTIA Network+ study guide : Exam N10-008 - Lammle, Todd (Sybex, a Wiley brand, 2022)
"Prepare for the Network+ certification and a new career in network installation and administration In the newly revised Fifth Edition of CompTIA Network+ Study Guide Exam N10-008, bestselling author and network expert Todd Lammle delivers thorough coverage of how to install, configure, and troubleshoot today's basic networking hardware peripherals and protocols. This book will prepare you to succeed on the sought-after CompTIA Network+ certification exam, impress interviewers in the network industry, and excel in your first role as a junior network administrator, support technician, or related position. The accomplished author draws on his 30 years of networking experience to walk you through the ins and outs of the five functional domains covered by the Network+ Exam N10-008: Networking fundamentals, implementations, operations, security, and troubleshooting. You'll also get: Complete, domain-specific coverage of the updated Network+ Exam N10-008 Preparation to obtain a leading network certification enjoyed by over 350,000 networking professionals Access to a superior set of online study tools, including practice exams, flashcards, and glossary of key terms."--